REPUTASI KANTOR AKUNTAN PUBLIK SEBAGAI PEMODERASI PENGARUH PROFITABILITAS DAN SOLVABILITAS PADA AUDIT DELAY - Wulandari, Ni Putu Winda; Utama, I Made Karya (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of profitability and solvency to audit delay, and to determine whether the reputation capable public accounting firms in the moderating influence of the profitability and solvency of the audit delay. This research was conducted on a property company listed on the Indonesia Stock Exchange (BEI) during the period 2011-2014. The number of samples obtained as many as 80, with purposive sampling method. Independent variables used in this study is the profitability and solvency. The dependent variable used is audit delay. Moderating variables used are reputable public accounting firms. The analysis technique used Moderated Regression Analysis (MRA). The results showed profitability and solvency effect on audit delay. Reputation public accounting firms can not moderate profitability in audit delay. Reputation public accounting firms can not moderate effect on the solvency of the audit delay.
Keywords: profitability, solvency, reputation KAP, audit delay